Comparative analysis of the impact of 40 adenovirus types on dendritic cell activation and CD8+ T cell proliferation capacity for the identification of favorable immunization vector candidates - Wang, Xiaoyan; Hetzel, Mario; Zhang, Wenli; Ehrhardt, Anja; Bayer, Wibke (Frontiers in Immunology, 2023)
For the development of new adenovirus (AdV)-based vectors, it is important to understand differences in immunogenicity. In a side-by-side in vitro analysis, we evaluated the effect of 40 AdV types covering human AdV (HAdV) species A through G on the expression of 11 activation markers and the secretion of 12 cytokines by AdV-transduced dendritic cells, and the effect on CD8 + T cell proliferation capacity. We found that the expression of activation markers and cytokines differed widely between the different HAdV types, and many types were able to significantly impair the proliferation capacity of CD8 + T cells. Univariate and multivariate regression analyses suggested an important role of type I interferons in mediating this suppression of CD8 + T cells, which we confirmed experimentally in a proliferation assay using a type I interferon receptor blocking antibody. Using Bayesian statistics, we calculated a prediction model that suggests HAdV types HAdV-C1, -D8, -B7, -F41, -D33, -C2, -A31, -B3 and -D65 as the most favorable candidates for vaccine vector development.